Relational Dialectics of Female K-Pop Boyband Fans with Parents and Friends in Medan City - Anjani, Vionita; Nurbani; Pohan, Syafruddin (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the relational dialectical process of K-Pop Boyband fans with their parents, analyze the relational dialectic process of K-Pop Boyband fans with friends and analyze the relational dialectical obstacles of female K-Pop Boyband fans with their parents and friends. The research methodology that researchers use is a qualitative research method with a constructivist paradigm. The research results obtained are that the relational dialectical process of female K-Pop Boyband fans with their parents and friends includes four basic elements and four assumptions that exist in the dialectical perspective. The contradictions present in this relationship are shown by different views towards K-Pop and organized by the four research informants through three categories in the dialectic of interaction.